2018
DOI: 10.1002/bem.22140
|View full text |Cite
|
Sign up to set email alerts
|

Ataxia telangiectasia mutated deficiency does not result in genetic susceptibility to 50 Hz magnetic fields exposure in mouse embryonic fibroblasts

Abstract: Extremely low frequency magnetic field (ELF-MF) has been classified as a possible carcinogen to humans by the International Agency for Research on Cancer [2002]. However, debate on the genotoxic effects of ELF-MF has continued due to lack of sufficient experimental evidence. Ataxia telangiectasia mutated (ATM) plays a central role in DNA damage repair; its deficiency can result in cellular sensitivity to DNA-damaging agents. To evaluate the genotoxicity of ELF-MF, we investigated the effects of 50 Hz MF on DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, we exposed the differentiation process to MF to evaluate the effects of 50‐Hz MF exposure on them. Since previous studies with Ames test, γH2AX focal assay, and micronucleus assay have reported that ELF‐MFs do not interact with DNA directly or indirectly or are associated with chromosomal translocations, unlike ionizing radiation [Jin et al, 2012 ; Morandi et al, 1996 ; Sun et al, 2018 ], we focused on the effects of MF exposure on the differentiation process to HSPCs. To draw a conclusion about the causal association of power‐frequency MFs and development of childhood leukemia, we need to accumulate data from experimental studies in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we exposed the differentiation process to MF to evaluate the effects of 50‐Hz MF exposure on them. Since previous studies with Ames test, γH2AX focal assay, and micronucleus assay have reported that ELF‐MFs do not interact with DNA directly or indirectly or are associated with chromosomal translocations, unlike ionizing radiation [Jin et al, 2012 ; Morandi et al, 1996 ; Sun et al, 2018 ], we focused on the effects of MF exposure on the differentiation process to HSPCs. To draw a conclusion about the causal association of power‐frequency MFs and development of childhood leukemia, we need to accumulate data from experimental studies in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic field exposure systems are designed to expose cell samples or devices to controlled magnetic fields and are widely used in scientific and industrial applications (Kirschvink, 1992). These systems can typically contain different coil geometries that act as passive elements for magnetic field generation such as solenoids (Han et al, 2018;Sanie-Jahromi and Saadat, 2018;Costantini et al, 2019;Samiei et al, 2020;Mansoury et al, 2021;Salek et al, 2021;Maleki et al, 2022;Mansoury et al, 2022), circular (Yuan et al, 2018;López et al, 2019;García-minguillán et al, 2020;Xu et al, 2020;Yuan et al, 2020;Asadian et al, 2021) or square (Consales et al, 2018;Sun et al, 2018;Zuo et al, 2020;Elexpuru-Zabaleta et al, 2023;Lazzarini et al, 2023) coils arranged in different configurations, such as the Merrit configuration (Kirschvink, 1992) or the Helmholtz configuration (Kirschvink, 1992;López et al, 2019;García-minguillán et al, 2020;Xu et al, 2020;Asadian et al, 2021;Cios et al, 2021;Lim et al, 2021). The latter is one of the most popular configurations for exposing cell cultures or small animals to ELF-EMF (López et al, 2019;Garcíaminguillán et al, 2020;Xu et al, 2020;Asadian et al, 2021;Cios et al, 2021;Lim et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the development of transgenic mice harboring ETV6‐RUNX1 , a translocation gene that is most frequently detected in childhood leukemia, and a pilot study with the transgenic mice for the evaluation of the effects of MFs were reported [Campos‐Sanchez et al, 2019]. Simultaneously, evaluations based on traditional carcinogenic mechanisms, such as mutagenicity, have been performed in in vitro studies where no relevance with power‐frequency MFs has been indicated [Morandi et al, 1996; Jin et al, 2012; Sun et al, 2018]. Additionally, in‐depth assessments regarding the impact on childhood leukemia, specifically pertaining to the effects on B‐progenitors and B‐cell early differentiation, are needed.…”
Section: Introductionmentioning
confidence: 99%